Representación computacional del lenguaje natural escrito - Ordoñez Salinas, Sonia; Gelbukh, Alexander (Ingeniería, 2010)
When humans read, or hear, words, they immediately relate them to a concept. This is possible due to the information already stored in the brain and also to human’s ability to select, process, and associate such information with words. However, for a computer, natural language text is only a sequence of bits that does not convey any meaning on its own, unless properly processed. A computer interprets this bit sequence by modeling the processing that takes place in human minds, namely structuring and linking the text with previously stored information. During this process, as well as when describing its results, the text is represented using various formal structures that permit automatic processing, interpretation, and comparison of information. In this paper, we present a detailed description of these structures.